Preventive Health Care Among Postpartum Women With Inflammatory Bowel Disease: Results From the PIANO Registry. Issue 4 (25th September 2018) - Mao, Eric J; Sheibani, Sarah; Martin, Christopher; Bloomfeld, Richard S; Isaacs, Kim; Saha, Sumona; Mahadevan, Uma
Abstract: Background: Health care maintenance (HCM) is reduced among inflammatory bowel disease (IBD) patients. This study aims to characterize rates of HCM in a closely monitored subpopulation—postpartum women with IBD—and identify predictors of noncompliance. Methods: A national prospective pregnancy registry was utilized to collect completion rates of HCM recommendations (cervical cancer screening; osteoporosis screening; pneumococcal, hepatitis A, hepatitis B, and influenza vaccines). Completion of a recommendation at least once during follow-up was sufficient, except for influenza vaccine, which was assessed yearly. Patients were classified by drug exposures: immunomodulator (Group A), biologic (Group B), combination therapy (Group AB), and unexposed. Confounders assessed were steroid exposure, IBD flare, IBD care site, primary care provider (PCP) access, marital status, income, education level, and race. Results: There were 628 postpartum IBD women with at least 1 year of follow-up. HCM rates were as follows: cervical cancer screening (84%), osteoporosis screening (54%), pneumococcal (50%), hepatitis A (61%), hepatitis B (81%), and influenza (72%) vaccines. The unexposed group demonstrated lower pneumococcal vaccination rates than groups A, B, and AB. Group B demonstrated lower cervical cancer screening rates than the unexposed. PCP access and low education predicted hepatitis vaccine noncompliance. Unmarried status and low income predicted cervical cancer screening noncompliance. Low income predicted influenza vaccine noncompliance. Conclusions: Postpartum women have multiple providers, yet they complete HCM at suboptimal rates. Risk factors include biologic exposure, unmarried status, low income, low education, and access to a PCP. Awareness among providers and patients is important and needs to be enhanced.